The effects of intelligent development and personality development in communications oral skills - Ibrahim, N.; Esa, Ahmad; Syed Iskandar, S. H. I.; Ahmad Jaafar, A. Z. (Elixir International Journal, 2017)
The purpose of this study was to relate the effect of intelligent development and personality development in communication oral skill. This article is based on the author’s reflections and interpretations on extended literature reviews. The author had a particular interest in relating both intelligent development and personality development through student’s co-curricular activity of debate. The debate orator’s cultures gives positive impacts on the development areas focused by the author.